Identification of Potential Environmentally Adapted Campylobacter jejuni Strain, United Kingdom - Will Sopwith; Andrew Birtles; Margaret Matthews; Andrew Fox; Steven Gee; Michael Painter; Martyn Regan; Qutub Syed; Eric Bolton (Emerging Infectious Diseases, 2008)
In a study of Campylobacter infection in northwestern England, 2003–2006, C. jejuni multilocus sequence type (ST)–45 was associated with early summer onset and was the most prevalent C. jejuni type in surface waters. ST-45 is likely more adapted to survival outside a host, making it a key driver of transmission between livestock, environmental, and human settings.